Impact of Management Measures on Multiple Ecosystem Function Trade-Offs and Their Dynamics in Subtropic Pinus massoniana Plantations - Zhang, Kexin; Zou, Hongzhu; Lei, Xiangdong; Zeng, Ji; Lan, Jie; Guo, Xiaoxue; Gao, Dongli; Liu, Xianzhao; Zhang, Huiru (Forests, 2024)
With the changing demands imposed on forests by human beings, optimizing forest management to fully utilize their multifunctionality has become a priority. Reasonable forest management measures can maintain stable forest ecosystems that fully coordinate the balance between ecological, societal, and economic aspects. As planted forests are the main application scenario of forest management worldwide, it is of great importance to understand the trade-offs between ecosystem functions and their dynamic changes in planted forests. This paper investigates the effects of different management measures on the ecosystem function of Pinus massoniana plantation forests in the subtropics. It examines four different management measures and explores how they impact multiple ecosystem function indexes and the trade-offs between ecosystem functions during forest restoration. The different management measures effectively promoted the studied ecosystem functions, with higher annual growth rates of the integrated functional indices for timber production, carbon sequestration, and biodiversity compared to the control. Over time, the ecosystem function interactions under the different management measures alternated between trade-offs and synergistic. Only the stand with a 65% harvesting intensity and replanting of various native broadleaf species was able to sustain the synergistic relationships among ecosystem functions, and the dominant function trended toward biodiversity. These observations of dynamic changes and interactions in ecosystem functions of Pinus massoniana plantation forests under various management measures will serve as a valuable reference for the sustainable management of these forests in subtropical regions.